Clinical applications of monitoring immune status with 90 immune cell subsets in human whole blood by 10‐color flow cytometry. (18th April 2021) - Wang, Weiwei; Li, Haibo; Zhang, Lihua; Jiang, Wenli; Shen, Lisong; Fan, Guang
Abstract: Introduction: The immune system may involve and predict the different prognosis and therapy consequences. So, it's important to monitor and evaluate the immune status before and after treatments. Methods: Flow cytometry is the best technology to perform immune monitoring, because it can detect immune cells using small amount of sample in a short time. The whole blood is the ideal sample for immune status monitoring, since it includes almost all the immune cells and it's relatively easy to obtain and less invasive than bone marrow or lymph node. Results: Here we developed and validated a 10‐color panel with only four tubes containing 29 antibodies to monitor 90 immune cell subsets in 2 ml whole blood samples. The major immune cell populations detected by our panel included T cell subsets (CD3 + total T, Th, Tc, Treg, CD8 hi, CD8 low, αβTCR, γδTCR, naïve, and memory T), T cell activation markers (CD25, CD69, and HLA‐DR) and one immune checkpoint PD1, B cell subsets (B1, switched memory, non‐switched, naïve B, and CD27 ‐ IgD ‐ B cells), neutrophils, basophils, four monocytic cell subsets, dendritic cells (pDCs and mDCs), and four NK cell subsets. These panels of antibodies had been applied to monitor immune status (percentage and absolute number) in total 303 cases with various diseases, such as leukemia (AML, CML, MM, and ALL), lymphoma (B cells and NK/T cells), cancers (colon, lung, prostate, and breast), immune deficiencies, and autoimmune diseases. Conclusion: We provided proof of feasibility for clinical monitoring immune status and guiding immunotherapy by multicolor flow cytometry testing.